Analysis of Liquidity, Solvency, and Activity on Profitability in Oil and Gas Sub-Sector Companies Listed on the IDX for the 2020-2023 Period - Allawiyah, Fatimah Zahro; Hertina, Dede (Almana : Jurnal Manajemen dan Bisnis, 2025)
Welcoming the readiness of energy security in Indonesia, oil and gas sub-sector companies must be ready to face this situation. This readiness is seen from the financial aspect of the company. Good financial performance is seen from the profit growth which is the benchmark for a company's performance. The higher the profit achieved by the company indicates the better the company's performance. If the company's financial ratio is good, then the company's profit growth is also good. The purpose of this study is to determine the Analysis of Liquidity, Solvency, and Activity on Profitability. This research was conducted on Oil and Gas Sub-sector Companies listed on the Indonesia Stock Exchange for the 2020-2023 period. The population in this study was 47 companies, using purposive sampling a sample of 16 companies. This research method uses quantitative description. The result is that liquidity affects profitability, solvency does not affect profitability and activity does not affect profitability.